Nutrient Evaluation of Fermented Amorphophallus campanulatus as Poultry Feed - Koni, Theresia Nur Indah; Zuprizal; Rusman; Hanim, Chusnul (International Journal of Poultry Science, 2017)
Background and Objective: Amorphophallus campanulatus (AC) can be used for food and as animal feed but its utilization is limited because of the high content of oxalate and low crude protein it contains. Fermentation by oxalolytic bacteria such as Bacillus subtilis (B. subtilis), which produce the oxalate decarboxylase enzyme, has been used to improve the nutritive value of AC. The present study was conducted to improve the nutritive quality of AC through fermentation using Bacillus subtilis. Materials and Methods: AC was incubated for three different lengths of time 7, 14 and 21 days with 3 replicates of each treatment. The parameters observed included the dry matter, crude protein, fat and fiber contents, as well as Ca, P and oxalate contents. Data obtained were subjected to analysis of variance using a completely randomized design. Results: Results showed that the length of the incubation period significantly affected oxalate content (p<0.05). Fermentation with Bacillus subtilis decreased the oxalate content of Amorphophallus by 53.2, 50.4 and 41.2% at 7, 14 and 21 days of incubation time, respectively, when compared with raw Amorphophallus (315.8 mg/100 g) and increased crude fat content (p<0.05). Additionally, the lowest crude fat was found in AC with 14 days of incubation time. However, there were no significant effects on dry matter, crude protein, crude fiber, Ca and P (p>0.05). Conclusion: Fermentation using Bacillus subtilis with an incubation length of 7 days was the best treatment for improving the nutrient value of AC.